2022
DOI: 10.3389/fpls.2021.805614
|View full text |Cite
|
Sign up to set email alerts
|

Light-Engineering Technology for Enhancing Plant Disease Resistance

Abstract: Insect vector-borne diseases are a major constraint to a wide variety of crops. Plants integrate environmental light and internal signalings to defend dual stresses both from the vector insects and vector-transmitted pathogens. In this review, we highlight a studies that demonstrate how light regulates plants deploying mechanisms against vector-borne diseases. Four major host defensive pathways involved in the host defense network against multiple biotic stresses are reviewed: innate immunity, phytohormone sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 161 publications
(169 reference statements)
1
7
0
Order By: Relevance
“…Under the FRL condition, this is typical only for PS2. Thus, the opinion available in the literature that RL as mono-chromatic light enhances the protective functions of plants, possibly through the activation of phytohormone signaling pathways, has been experimentally confirmed on cucumber leaves [28].…”
Section: Discussionmentioning
confidence: 86%
“…Under the FRL condition, this is typical only for PS2. Thus, the opinion available in the literature that RL as mono-chromatic light enhances the protective functions of plants, possibly through the activation of phytohormone signaling pathways, has been experimentally confirmed on cucumber leaves [28].…”
Section: Discussionmentioning
confidence: 86%
“…All these results demonstrated that MAPKKK/MAPKK/MAPK-WRKY-CML/CDPK might indicate a new complex network in soybean for defense against SMV infection. By summarizing the PPI analysis in this study and combining it with previous reviews on the role of circadian rhythm in plant immunity ( Hua, 2013 ; Wang et al, 2021 ), we drew a model diagram of soybean resistance response to SMV ( Figure 8B ).…”
Section: Resultsmentioning
confidence: 99%
“…The G-box is a ubiquitous light regulatory element in many of the promoters [56] and is highly represented lightresponsive cis-element (279) among the EcNBLRRs promoters, followed by Box-4 (90), GT-1 (62) motif etc. Several studies have shown the essential roles of a particular spectrum of light in promoting plant defence against various pathogen infections [57]. For instance, the red-light spectrum enhances the plants' resistance to various pests and pathogens [58]; however, the detailed molecular basis still needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%